The concept of Islamic moderation in music art: Special reference to the song of nasyeed - Yusof, M. (2014)
The music art is not strange in Islam. It has been given serious attention by muslim scholars from time to time. Hence, many speculation among the muslim and non-muslim about the actual status of music in Islam. It happened because of the emergesce of various patterns of ·mus-i£·inthe -e-liltur-e ef.soeiety ·inthe medem world today. Therefore, this discussion tries to explain the concept of moderation and enjoyment of music as guided by Islam in order to fulfill the needs of human nature. In this case, nasyeed song is believe to achieve these objectives. Therefore, to determine the effect on the listener nasyid, the samples taken from the listener nasyid songs aired by Radio IKIM.fm. Radio IKIM.fm is the first radio channel based on Islam in Malaysia. A total of 707 respondents were given questionnaires. The results showed that nasyeed songs aired in Radio IKIM.fm give many positive effects, especially in the self-development of the listener.